Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, dan Konservatisme Akuntansi pada Tax Avoidance - Windaryani, I Gusti Agung Istri; Jati, I Ketut (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p08, 2020)
This study aims to obtain empirical evidence regarding the effect of company size, institutional ownership, and accounting conservatism on tax avoidance in the Mining Sector Companies contained on the Stock Exchange in the 2015-2018. The sample was determined using the nonprobability sampling method with a purposive sampling technique, obtained by 11 companies with a year of observation for 4 years so as to obtain 44 observations. Data analysis techniques using the Multiple Linear Regression test with the SPSS program. The research result that the size of company and accounting conservatism give a negative effect on tax avoidance while institutional ownership has no effect on tax avoidance. This shows that the larger the size of a company and the more companies apply accounting conservatism, the lower the practice of tax avoidance. Keywords: Company Size; Ownership Institutional; Accounting Conservatism; Tax Avoidance.